Empowering Future Civic Educators: Exploring the Impact of the Kampus Mengajar Program on Professional Competence Development through Nvivo Qualitative Analysis - Nurlaili, Novitasari Gemi; Prasetiyo, Wibowo Heru (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
The swift evolution of our era has revolutionized education, necessitating well-prepared teachers to navigate the challenges of the 5.0 society. The Teaching Campus or Kampus Mengajar program (KM) stands as a governmental initiative addressing these global challenges. This study delves into the role of the KM program within the Civic Education Study Program, specifically examining its influence on the professional competence of aspiring teachers. Employing a qualitative approach with a descriptive design, this research aims to elucidate the impact of KM on students' professional development. Purposive sampling was utilized to recruit informants, and semi-structured interviews, complemented by documentation and Focus Group Discussions (FGD), were employed for data collection. Face-to-face interactions and member checking were integral to ensuring data validity. The study unveils that the 4th, 5th, and 6th KM programs effectively propel aspiring teachers towards professionalism by fostering competencies and realizing the program's objective of enhancing literacy and numeracy in students. The findings and recommendations presented herein offer valuable insights for future researchers endeavoring to explore and develop similar studies in the realm of teacher preparation programs.